How does economic crisis impact on family vacations? - Pereira, H. G. (2018)
PURPOSE: This study aims at improving the understanding of the behavior of Portuguese consumers regarding vacations in a severe recessionary context, as well as providing knowledge contributing to the consumer behavior field of research as far as the hospitality industry is concerned. DESIGN: Having that purpose in mind, a quantitative study was conducted using data gathered by questionnaire involving a sample of 450 respondents. Results of the quantitative analysis were further complemented with the information previously collected using Netnography. FINDINGS: The overall analysis suggests that the impact of the crisis on the household financial situation throughout the last couple of years influences decisions towards family vacations. When referring to attitudes toward money and expenses, the perception consumers have of how much their purchase and consumption behavior was affected by the crisis has a clear impact to the maximum amount spent on holidays, travel and tourism by the household. Indeed, nowadays customers better ponder every purchase they make, and they often imagine what they would do if they had more money – and, specifically, regarding tourism products. PRACTICAL IMPLICATIONS: There is evidence of a significant relationship between the change in holiday plans and how much the household was affected by the crisis. Also, it is important to note that the main sources of information chosen by customers to base their decisions regarding changing holiday’s plans reflects their change in behavior, since the cheapest strategies to communicate and gather information are the ones most used: e-word of mouth and digital platforms.